Rediscovering Pertussis - Zlamy, Manuela (Frontiers in Pediatrics, 2016)
Pertussis, caused by Bordetella (B.) pertussis, a Gram-negative bacterium, is a highly contagious airway infection. Especially in infants pertussis remains a major health concern. Acute infection with B. pertussis can cause severe illness characterized by severe respiratory failure, pulmonary hypertension, leucocytosis and death. Over the last years rising incidence rates of intensive care treatment in young infants were described. Due to several virulence factors (pertussis toxin, tracheal cytotoxin, adenylate cyclase toxin, filamentous hemagglutinin, lipooligosaccharide) which promote bacterial adhesion and invasion B. pertussis creates a unique niche for colonization within the human respiratory tract. The resulting long-term infection is mainly caused by the ability of B. pertussis to interfere with the host’s innate and adaptive immune system. Although pertussis is a vaccine-preventable disease it has persisted in vaccinated populations. Epidemiological data reported a worldwide increase in pertussis incidence among children during the last years. Either acellular pertussis vaccines or whole-cell vaccines are worldwide used. Recent studies did not detect any differences according pertussis incidence comparing the different vaccines used. Most of the currently used acellular pertussis vaccines protect against acute infections for a period of 6-8 years. The resurgence of pertussis may be due to the lack of herd immunity caused by missing booster immunizations among adolescents and adults, low vaccine coverages in some geographic areas and genetic changes of different B. pertussis strains. Due to the rising incidence of pertussis probable solution strategies are discussed. Cocooning strategies (vaccination of close contact persons) and immunizations during pregnancy appear to be an approach to reduce neonatal contagiousness. During the last years studies focused on the pathway of the immune modulation done by B. pertussis to provide a basis for the identification of new therapeutic targets to enhance the host’s immune response and to probable modulate certain virulence factors.